Stress distributions in bluntly-notched ceramic composite laminates - Rajan, Varun P.; Zok, Frank W. (Composites. Part A, Applied science and manufacturing, 2014)
We present a methodology for determining stress distributions ahead of blunt notches in plates of fiber-reinforced ceramic–matrix composites subject to uniaxial tensile loading, accounting for the effects of inelastic straining due to matrix cracking. The methodology is based on linear transformations of the corresponding elastic distributions. The transformations are derived from adaptations of Neuber’s law for stress concentrations in inelastic materials. Comparisons are made with results computed by finite element analysis using an idealized (bilinear) form of the Genin–Hutchinson constitutive law for ceramic composite laminates. Effects of notch size and shape as well as the post-cracking tangent modulus are examined. The comparisons show that, for realistic composite properties, the analytical solutions are remarkably accurate in their prediction of stress concentrations and stress distributions, even in cases of large-scale and net-section inelasticity. Preliminary assessments also demonstrate the utility of the solution method in predicting the fields under multiaxial stressing conditions.